Elucidation of the phenotypic spectrum and genetic landscape in primary and secondary microcephaly - Boonsawat, Paranchai; Joset, Pascal; Steindl, Katharina; Oneda, Beatrice; Gogoll, Laura; Azzarello-Burri, Silvia; Sheth, Frenny; Datar, Chaitanya; Verma, Ishwar C.; Puri, Ratna Dua; Zollino, Marcella; Bachmann-Gagescu, Ruxandra; et al. (Genetics in Medicine, 2019)
Purpose: Microcephaly is a sign of many genetic conditions but has been rarely systematically evaluated. We therefore comprehensively studied the clinical and genetic landscape of an unselected cohort of patients with microcephaly. Methods: We performed clinical assessment, high-resolution chromosomal microarray analysis, exome sequencing, and functional studies in 62 patients (58% with primary microcephaly [PM], 27% with secondary microcephaly [SM], and 15% of unknown onset). Results: We found severity of developmental delay/intellectual disability correlating with severity of microcephaly in PM, but not SM. We detected causative variants in 48.4% of patients and found divergent inheritance and variant pattern for PM (mainly recessive and likely gene-disrupting [LGD]) versus SM (all dominant de novo and evenly LGD or missense). While centrosome-related pathways were solely identified in PM, transcriptional regulation was the most frequently affected pathway in both SM and PM. Unexpectedly, we found causative variants in different mitochondria-related genes accounting for 5% of patients, which emphasizes their role even in syndromic PM. Additionally, we delineated novel candidate genes involved in centrosome-related pathway (SPAG5, TEDC1), Wnt signaling (VPS26A, ZNRF3), and RNA trafficking (DDX1). Conclusion: Our findings enable improved evaluation and genetic counseling of PM and SM patients and further elucidate microcephaly pathways.
CRIS-Team Scopus Importer:2019-09-17
Keywords: genetic counseling; MCPH; mitochondria; primary microcephaly; secondary microcephaly